Resenha de La serpiente sin ojos (Ospina, 2012) (2017)
Andrello, G. (2006). Cidade do índio. Transformações e cotidiano em Iauaretê. São Paulo: Editora UNESP – ISA; Rio de Janeiro: NUTI. 447 pp. ISBN: 8571396590.